(untitled) (International Journal of Engineering and Computer Science, 2017)
The actual meaning of Benami is without a name. The word “Benami” means buying property in the name of another person. However, when you are making a purchase, you are not purchasing a plot on your name. You are purchasing this plot on the name of close relatives. The property purchased like this will be considered as a Benami property. The holder of the property is known as benamidar. In this paper, we introduce an Uniform Cost Search algorithm for efficient searching of benamidar. The benamidar is a person who has the movable and immovable, tangible, intangible, any right or interest, or legal documents asserts of another person in their name. As such, even gold or financial securities including bank accounts could qualify to be Benami. To identify the benamidar, the details of Aadhar card, the details of PAN card, the details of asserts and details of Bank are filled and stored. The interlink of Aadhar card, PAN card, asserts and Bank account is done. The mining of details is done by generating family tree and by pruning the person is being extracted. Each property is linked with Aadhar card so that on examining the details will help to find the benamidar by the Income Tax Officer.